Features of the development of contemporary Chinese, Korean and Japanese art and cinema - T. K. Ognieva, (Ukrainian Cultural Studies, 2020)
The article analyzes the conditions and factors that influenced the formation of contemporary art and cinema in China, South Korea and Japan. We can determine the peculiarities of the development of Chinese contemporary art, such as the desire of the first artists, after the Cultural Revolution, to reflect its flux and effects as much as possible. Further, artistic tendencies become diverse: the commercial component and a certain element of the state of affairs are viewed in the works of art by Chinese authors, but the desire for self-expression in different ways testify to the progressive phenomena characteristic of art.Modern Korean art proves that the scientific and technological revolution and the dominant avant-garde component of mass culture in general cannot supplant the ultimate traditional artistic creativity. One of the characteristic features of contemporary Korean art is a demonstration of belonging to the culture of the country. First of all, this is the influence of the traditions of Confucianism, Buddhism, along with the painful memories of war and long-term colonization by Japan. One can note the simplicity, orderliness, harmony of colors and shapes as an inalienable feature of Korean contemporary art, but modern tendencies show the striving for the discovery of individuality of the artist, which manifests itself in non-standard artistic forms.Japanese visual art combines the works of autochthonous traditions and European artistic principles. Considerable attention is paid to the issue of the relationship between nature and man, reflected in the work of adherents of the synthesis of Japanese traditions and Western variety of forms. Particular attention is paid to contemporary artists in Japan with the latest technology – video art, 3D painting, interactive installations and installations-hybrids.Chinese cinema with the generation of directors, known as the Fifth Generation, reveals new trends. These artists initially sought to convey events and tragedies during the Cultural Revolution, but over time they turned to other themes and genres. Directors of the "Sixth Generation" paid special attention to social problems, the place of action in their films is unknown China – small settlements or cities.Modern Korean cinema covers two large areas: cinema for women – melodrama, and for men – adventure. Today the adventure genre is oriented mainly to teens, and the melodrama genre has been transformed from the problems of the middle-aged women's interest towards the youth audience, therefore, it is more likely to come closer to the romantic comedy.The tragedy of Korea, which is split up into two parts, worries the movie-makers. In recent years there have been changes in South Korean position in exposing North Korean residents. If the previous decades in South Korean cinema was cultivating the image of the enemy: North Korean could be either a spy or killer, but now the inhabitants of North Korea are perceived and presented in films differently, not embodying exclusively negative features.In Japanese cinema, the emphasis is on the visual array, which allows you to bring forward contemplation and the deep meaning is transmitted by artistic images typical of the oriental art in general. In films, much attention is paid to the smallest details; certain asceticism along with the aesthetization of the frame is a reflection of purely Japanese features – minimalism as the meaning of existence.Familiarity with the peculiarities of the development of contemporary art and cinema in China, Korea and Japan is a necessary component for further dialogue between the cultures of East and West in terms of balanced interaction and artistic transformations of the modern world.
Keywords: contemporary art, China, Korea, Japan, cinema